1995
DOI: 10.1111/j.1095-8649.1995.tb06022.x
|View full text |Cite
|
Sign up to set email alerts
|

On the life‐history of Atractoscion aequidens, a migratory sciaenid off the east coast of southern Africa

Abstract: East coast geelbek exist as a single stock comprising three distinct age/size structured subpopulations. The subadults (1-4 years) occur in the SW Cape, South Africa. They feed principally on anchovy Engruulis cupensis, which they follow inshore in summer and offshore in winter. The adults (5-9+ years) undergo a seasonal inshore and longshore migration to Natal where they spawn offshore in spring. During this migration they feed mainly on the pilchard Surdinops sugax, which also move north-eastwards during thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 14 publications
3
41
0
Order By: Relevance
“…However, some species have predictable migrations (Griffiths and Hecht 1995), whereas others disperse unpredictably (Attwood and Bennett 1994). Although many South African sparids are resident throughout their lives Allen 1989, Cowley et al 2002), the longshore migrations of adult red steenbras observed in this study support Smale's (1988) suggestion that they migrate to the Transkei Coast.…”
Section: Discussionsupporting
confidence: 50%
“…However, some species have predictable migrations (Griffiths and Hecht 1995), whereas others disperse unpredictably (Attwood and Bennett 1994). Although many South African sparids are resident throughout their lives Allen 1989, Cowley et al 2002), the longshore migrations of adult red steenbras observed in this study support Smale's (1988) suggestion that they migrate to the Transkei Coast.…”
Section: Discussionsupporting
confidence: 50%
“…migrate from the Cape waters to KwaZulu-Natal at the same time as do adult dusky kob (Griffiths 1996). These concurrently migrating prey species may provide an important source of energy for both migration and gonad development, as has been shown for S. sagax and the migratory sciaenid Atractoscion aequidens (Griffiths and Hecht 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Other sciaenids, e.g. Argyrosomus japonicus (Smale 1985), Atractoscion aequidens (Griffiths & Hecht 1995) were predominately tagged at the southern end. The bathymetry and morphology of the channel where individual P. diacanthus were present is likely to have influenced the ability of the receiver to detect the fish, and also the fish's behaviour (see discussion of tidal influence).…”
Section: Discussionmentioning
confidence: 99%